The Theoretical and Methodological Bases of Strategic Planning for the Development of Ukrainian Regions - Kondratenko Nataliia O.; Сhechetova Natalia F.; Obolentseva Larysa V.; Krasnonosova Olena M. (Problemi Ekonomiki, 2022)
The article generalizes the theoretical and methodological bases of strategic planning for the development of regions of Ukraine and develops a mechanism for strategic planning (SP) for the development of territories. It is determined that strategic planning for the development of regions is a very important instrument of the State-based regulation, which helps to maintain all the necessary economic proportions, ensures the scheduled functioning of all parts of the economic system of society. For the Ukrainian economy, strategic planning is very relevant and important, as it allows predicting the processes of privatization and demonopolization, the formation of various forms of asset ownership, the consequences of technological renewal of production and much more. As the economy stabilizes, the possibilities of identifying trends and regularities of regional development spread, the degree of predictability of changes and behavior of various economic entities increases. It is noted that in modern regional management there is a shortage in scientific support of development conceptions, targeted planning of the regional economy. Insufficiently developed are technologies for the formation of scenarios for socioeconomic development, as well as instruments of public-private partnership. The issues of applied nature concerning the use in practice of strategic planning and the mechanism for forming a strategy for the socioeconomic development of the region require further theoretical and methodological development. It is concluded that the existing problems of increasing the efficiency of strategic planning for the development of Ukrainian regions can be solved on the basis of the introduction of an effective mechanism, which remains in its infancy today. The proposed mechanism of strategic planning for the development of territories will allow both in theory and in practice to improve the quality of life of the population, will affect the reduction of mortality rates, increase the level of ecological safety, promote the development of priority industries, and generally increase the competitiveness of regional economic systems